2021
DOI: 10.1111/ijcp.14398
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID‐19 pandemic on paediatric emergency service

Abstract: Aims The aims of this research were to review patients visiting the paediatric emergency department over a 6‐month period 1 year before and during the pandemic, to review paediatric emergency department referral ratios and to determine whether there were any significant decreases in mortality and morbidity. Methods All patients from the ages of 0 to 18 years visiting the University of Health Sciences, Ankara Research and Training Hospital, paediatric emergency service f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Pediatric emergency department visits fell more sharply than adult ED visits during the COVİD-19 pandemic. This finding is in line with the results of other relevant studies available in the literature [10,11,12]. The decrease in the number of pediatric emergency admissions for non-COVID-19 diseases was attributed to the fear of contracting COVID-19 from the hospital, that is, parents preferred not to bring their children to the hospital unless the condition of their children has aggravated [12,13,14].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Pediatric emergency department visits fell more sharply than adult ED visits during the COVİD-19 pandemic. This finding is in line with the results of other relevant studies available in the literature [10,11,12]. The decrease in the number of pediatric emergency admissions for non-COVID-19 diseases was attributed to the fear of contracting COVID-19 from the hospital, that is, parents preferred not to bring their children to the hospital unless the condition of their children has aggravated [12,13,14].…”
Section: Discussionsupporting
confidence: 88%
“…This finding is in line with the results of other relevant studies available in the literature [10,11,12]. The decrease in the number of pediatric emergency admissions for non-COVID-19 diseases was attributed to the fear of contracting COVID-19 from the hospital, that is, parents preferred not to bring their children to the hospital unless the condition of their children has aggravated [12,13,14]. On the other hand this reduction was the result of a decreasing in infectious disease.…”
Section: Discussionsupporting
confidence: 88%
“…1 , 47 studies were included in the systematic review (study characteristics are reported in Table 1 ). 32 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 Among these studies, 43 were included in the meta-analytical process, for a total of around 65 million subjects (suicides: 63,120,235; suicidal behaviors: 934,951; suicidal ideation: 156,234): two reporting rates of deaths for suicides, 48 , 50 26 reporting prevalence data about suicidal behaviors 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 <...…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from the Europe and Central Asia region included data from Turkey (n = 3 studies), and the Russian Federation (n = 2) [1, [23][24][25][26]. There was only 1 reasonable quality study, and this was the only study which directly reported on the impact of COVID-19 on suicide risk [1].…”
Section: Europe and Central Asiamentioning
confidence: 99%
“…admissions for self-harm changed during the pandemic, although there were 83% fewer presentations (Fig 3) [24].…”
Section: Plos Global Public Healthmentioning
confidence: 99%